Royal Commission into Family Violence: issues paper - Royal Commission into Family Violence
The purpose of this issues paper is to provide general guidance to individuals and organisations in making written submissions to the Royal Commission into Family Violence. Introduction The Royal Commission into Family Violence (‘the Royal Commission’) is seeking submissions from anyone directly affected by family violence, from individuals and organisations who have come into contact with people affected by family violence (whether directly working in the family violence sector or not), and from any others whose experiences and ideas may assist the work of the Royal Commission. Examples of individuals who do not work directly in the family violence sector but may wish to make a submission include general practitioners and other health professionals, social workers, disability workers and advocates, teachers and community or religious leaders. The purpose of this issues paper is to provide general guidance to individuals and organisations in making their written submissions. The Royal Commission is also accepting submissions that address its Terms of Reference1 without responding to the particular questions in this issues paper. Written submissions are just one of the ways in which the Royal Commission will gather views and information. It will also be examining more detailed questions through its research, community engagement and public hearing activities. Updates about the Royal Commission’s activities will appear on our website: www.rcfv.com.a